The effects of direct and indirect written corrective feedback on the use of present tenses among ESL learners / Chieng Shea Lee - Chieng, Shea Lee (2014)
This study investigated the effectiveness of different strategies of written corrective feedback in improving students' written accuracy. 20 students were recruited and divided into two groups, direct and indirect group. This study was conducted in 3 stages; pre-test, treatment, and post-test. Feedback was provided in treatment stage where group one students received direct corrective feedback while group two students received indirect corrective feedback. The errors made on each stage were marked and counted to be used to compare among each stage of their writings as well as between the two groups. The results showed that students who received direct corrective feedback outperformed students who received indirect corrective feedback in the post-test. In addition, the results also showed that although the mean number of errors made by indirect feedback group did not decrease in post-test, the mean number of errors made decrease in their revised texts. Thus, it can be concluded that indirect corrective feedback was an effective tool in helping students retaining their language learning over a period of time. Interviews were also conducted to gain insights on other factors that affect students’ writing performance. Based on the results gained, two themes which influence the effectiveness of written corrective feedback on students’ writing are motivation and scaffolding. Three anecdotal findings were also collected through the interviews. They are related to students expressing their concern on content-related knowledge when writing an essay. In addition, students also stated that teachers should apply mix strategies when correcting different types of errors made by the students based on the severity. Last, but not least, the interview also revealed the impact of students’ exam-orientedness on their language learning. The results of the study suggest that to some extent, written corrective feedback is effective in reducing students’ error in their writing. From the findings, some recommendations are made at the end of this report.